Detecting cardiac troponin T forms in advanced chronic kidney disease patients - Kaipainen, Emilia (My University, 2024)
Cardiac troponin T (cTnT) immunoassays are widely used in the diagnostics of myocardial infarction. Chronic kidney disease (CKD) is a progressive disease in which the filtration rate of kidneys is impaired. CKD patients have stable elevations of cTnT in their bloodstream. Circulating cTnT is in fragmented forms in end-stage renal disease while in myocardial infarction cTnT is found in long molecular forms. Forms of cTnT in advanced CKD have not been studied. The aim of this study was to develop an immunoassay for total cTnT measurement and to determine the amount of total cTnT and long cTnT in advanced CKD patient samples. In the development of the total cTnT assay, different biotinylated and upconverting nanoparticle (UCNP) conjugated antibody combinations were evaluated in a heterogeneous sandwich immunoassay. Heparin plasma samples from cardiac patients with known commercial total cTnT test results were used for the assay development. The advanced CKD patient heparin plasma sample panel (n=152) was analyzed with the optimized total cTnT assay and with an assay detecting only long forms of cTnT. The antibodies which gave the best concentration correlation to a commercial total cTnT assay were chosen (Spearman’s r 0.90) for the total cTnT assay. Analytical detection limit of 0.5 ng/L (zero calibrator+3 standard deviation) was reached with the optimized total cTnT assay. The CKD patient sample panel results for the total cTnT assay were (median [25th–75th percentile]) 38.7 [23.2–69.9] ng/L and for the long cTnT assay 1.9 [1.2–2.9] ng/L. The fraction of long cTnT in total cTnT was 4.2 [3.2–6.6] %. The results confirmed that advanced CKD patients have elevated total cTnT concentrations, but this was the first study to reveal that this elevation is predominantly caused by short cTnT fragments. The study highlights that if CKD patients are diagnosed with long cTnT test instead of total cTnT test, the diagnosis of possible myocardial infarction can be confirmed rapidly.
Keywords: cardiac troponin T, chronic kidney disease, UCNP